2023
DOI: 10.3390/children10020311
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Use in Pediatric Care during the COVID-19 Pandemic: A Qualitative Study on the Perspectives of Caregivers

Abstract: This qualitative study surveyed caregivers regarding their perspectives on the benefits of, challenges with, and suggestions for improving telehealth during the COVID-19 pandemic. Caregivers who had the responsibility for caring for at least one child aged under 18 years of age in Genesee County, MI, participated. The caregivers were biological parents, stepparents, foster parents, adoptive parents, and guardians. A total of 105 caregivers completed a survey with open-ended questions via Qualtrics. Two indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Families also saw telehealth as an additional way to protect their child's physical health by limiting potential contact with illnesses through decreasing time spent in healthcare settings—an idea well‐supported by both prepandemic and pandemic‐related literature on the use of telehealth in a population of CMC (Diskin et al, 2022; Mosquera et al, 2021; Onofri et al, 2021). Of note, some extant literature suggests more challenges with pediatric telehealth, such as parental privacy concerns and technology issues (Aultman et al, 2023; Kodjebacheva et al, 2023), which were not represented in the current findings. Although the current study's results may not fully capture the experiences of all families of CMC, they suggest potential opportunities for improved access of care within the context of CCPs.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Families also saw telehealth as an additional way to protect their child's physical health by limiting potential contact with illnesses through decreasing time spent in healthcare settings—an idea well‐supported by both prepandemic and pandemic‐related literature on the use of telehealth in a population of CMC (Diskin et al, 2022; Mosquera et al, 2021; Onofri et al, 2021). Of note, some extant literature suggests more challenges with pediatric telehealth, such as parental privacy concerns and technology issues (Aultman et al, 2023; Kodjebacheva et al, 2023), which were not represented in the current findings. Although the current study's results may not fully capture the experiences of all families of CMC, they suggest potential opportunities for improved access of care within the context of CCPs.…”
Section: Discussionmentioning
confidence: 64%
“…Families also saw telehealth as an additional way to protect their child's physical health by limiting potential contact with illnesses through decreasing time spent in healthcare settings-an idea well-supported by both prepandemic and pandemicrelated literature on the use of telehealth in a population of CMC (Diskin et al, 2022;Mosquera et al, 2021;Onofri et al, 2021). Of note, some extant literature suggests more challenges with pediatric telehealth, such as parental privacy concerns and technology issues (Aultman et al, 2023;Kodjebacheva et al, 2023) Although a purposive sampling technique was used to attempt to recruit a diverse group of participants, sampling was based on child demographics which may differ from caregiver demographics. Furthermore, only English-speaking families were included in the study, resulting in a lack of understanding of these pandemic-related experiences among families who primarily speak other languages.…”
Section: Discussionmentioning
confidence: 99%
“…They may assess the effectiveness of telehealth compared to in-person services on satisfaction, quality of life, and health outcomes among youth. Parents expressed a preference of using video compared to in-person consultations for their children and adolescents due to the fear of contracting COVID-19 in past qualitative research during the pandemic ( 62 ). Future interviews with adolescents may ask regarding preferences for using remote compared to in-person care following the COVID-19 pandemic when fear of contracting a virus may not be as elevated.…”
Section: Discussionmentioning
confidence: 99%
“…One review of various telehealth methods (SMS, email, social media, video calls, phone calls, web-based systems, or apps) found that most parents had an overall positive experience with using digital health technology in pediatric overweight and obesity [24], reporting that they saved time and money on travel and found it to be generally convenient. A survey of caretaker opinions regarding telehealth conducted during the COVID-19 pandemic listed quality communication with physicians, savings in travel time, and cost-effectiveness, yet identified challenges such as lack of in-person interaction (as we also certainly felt in the clinic), fear of compromised confidentiality, and the potential for misdiagnosis [25]. Collectively, telehealth in obesity treatment is clinically useful and has its benefits, but it still requires some refining.…”
Section: Discussionmentioning
confidence: 99%
“…Telehealth was selected more often for follow-up visits compared with initial visits, just as we felt as well. Moreover, another downside of video chats was the difficulty to create a person-to-person relationship, as stated above [25]. We, hence, recommend that specialist pediatric obesity clinics be able to provide all forms and levels of care by having all clinical personnel needed, with face-to-face, video chats, apps, or automated reminders/messages options in their toolbox, tailored to each family's needs and preferences.…”
Section: Discussionmentioning
confidence: 99%